Social Media and Collective Identity Movement: Representation of Hizbut Tahrir Subculture in Indonesia - Chakim, Sulkhan (International Conference of Moslem Society, 2018)
Social movement is a tool to achieve the ultimate goal, as well as the media used is as a tool to mobilize amongst people. This article contributes to the understanding of the social movements of the subculture and media cyber, as well as its implications for society on socio-religious movements. Based on qualitative research conducted in 2017 through textual analysis and response of HizbutTahrir members in every discourse by Hizbut Tahrir’s online. Hizbut Tahrir's online issues represent the subculture as a social movement depicting the collective social identity of major issues that related to different countries and general flows. Online media are able to mobilize actors to the grassroots level to reject the policies and concepts of statehood, and even the rejection of non-Muslim government leadership. The issue of this article is how online media influence, construct the identity of certain groups in socio-religious, and political issue.